The Role of Spatial Design in Shaping Cinematic Narrative and Experience - Keshwala, Jayesh M.; Qureshi, Vaseemahmed G. (Journal of Ecohumanism, 2025)
This study provides an insight into how the spatial design plays an important role in shaping cinematic narrative and audience experience, with a particular focus on backdrop and locale as the concealed yet powerful narrative devices. Often overlooked, these powerful visual elements enrich the fabric of cinematic universe by shaping viewers’ emotional and intellectual response. This research paper explores the multiple ways in which backdrop and location influence the film’s narrative, character development and audience engagement. After examining a variety of films across various genres, time periods, and cultural contexts, this paper investigates the intricate relationship between the setting and thematic impact of films. This paper also examines how filmmakers utilize the spatial design not only as decorative elements but also as dynamic, expressive agents that impact the story arcs, emotional ambience and world-building coherence. The first part of this paper explores and establishes the concept of backdrop and locale within the context of films. The second part delves into the impact of backdrop and locale, particularly on the narrative, characters, and the audience to understand the significance of these hidden gems in the cinematic universe.